EGFR exon 19‐deletion aberrantly regulate ERCC1 expression that may partly impaired DNA damage repair ability in non‐small cell lung cancer. Issue 2 (25th December 2019) - Zhang, Linlin; Pradhan, Barun; Guo, Lili; Meng, Fanlu; Zhong, Diansheng
Abstract: Background: Epidermal growth factor receptor (EGFR) activating mutations are usually associated with DNA damage repair (DDR) deficiency. However, the precise mechanism has remained elusive. In this study, we aimed to investigate whether EGFR exon 19 deletion mutation downstream signals contributed to DDR deficiency by downregulation of excision repair cross‐complementation group‐1 (ERCC1), a key factor in DDR, expression and function. Methods: We first measured cell survival, DNA damage (γ‐H2AX foci formation) and damage repair (ERCC1 and RAD51 foci formation) ability in response to DNA cross‐linking drug in EGFR exon 19 deletion and EGFR wild‐type cells separately. We then investigated the involvement of EGFR downstream signals in regulating ERCC1 expression and function in EGFR exon 19 deletion cells as compared with EGFR wild‐type ones. Results: We observed increased γ‐H2AX, but impaired ERCC1 and RAD51 nuclear foci formation in EGFR exon 19 deletion cells as compared with EGFR wild‐type ones treated with DNA cross‐linker. In addition, we identified that inhibition of EGFR exon 19 deletion signals increased ERCC1 expression, whereas blocked wild‐type EGFR signals decreased ERCC1 expression, on both mRNA and protein levels. Furthermore, EGFR exon 19 deletion downstream signals not only inhibited ERCC1 expression but also influenced ERCC1 foci formation in response to DNA cross‐linker. Conclusion: Our findings indicated that the aberrant EGFR exon 19 deletion signals were not only associated with decreased expression of ERCC1 but were also involved in impaired ERCC1 recruitment in response to DNA cross‐link damage, thereby providing us with more evidence for exploring the mechanism of DDR deficiency in EGFR mutant NSCLC.